A Methods engineering study on Doña Adela Export International, Inc. - Bacud, Marie Joanne B.; Buyco, Joyce Dawn S.; Ko, J-Za A. (Diliman, Quezon City College of Engineering, 2001)
Doña Adela Export International Inc., located in Mandaluyong City, manufactures children's garments. General processes involved in manufacturing were the considered in this study. A time study was not conducted due to the wide variety of designs and styles and their different complexities of the processes. For the purpose of the process documentation, only one particular design was considered by the group. Through brainstorming and the use of Streamline Diagnosis Chart, the following major problems were identified : inefficient layout, inadequate lighting intensity, and non-availability of machines for transportation between floors. At most four alternatives were generated for the aforementioned problems. A common alternative for the three problems is to do nothing. It is suggested that a new production area layout be adapted for easier process and material flow. Addition of more lamps is suggested for inadequate light problem since it yields the cheapest cost among the alternatives generated. For transport of materials problem, a proposed design for the transport machine to be installed is suggested. All the alternatives were evaluated using the Kepner-Tregoe Decision Analysis and Cost-Benefit Analysis. Evaluation of alternatives shows the effects of the alternatives of the company. Finally, implementing steps for each recommendation was presented and the preventive and contingency actions to be made
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis